Examining Instagram uses & gratification on followers @pandemictalks - Hindina Maulida (ARKA INSTITUTE, 2026)
The Covid-19 pandemic has driven an increase in public demand for health information that is fast, accurate, and easily accessible. Social media, particularly Instagram, has become one of the main sources for meeting this demand. This study aims to analyze the motives for using Instagram as a medium for searching for health information related to COVID-19 among followers of the @pandemictalks account using the Uses and Gratifications theory approach. The research method used was a quantitative approach with a survey technique of followers of the @pandemictalks account. The results showed that the main motives for using Instagram in this context included fulfilling information needs, increasing health knowledge, reducing uncertainty, and active engagement through user interaction and participation. These findings indicate that the @pandemictalks account plays a significant role as an alternative source of science-based health information amid the pandemic crisis. The novelty of this research lies in its focus on analyzing independent Instagram accounts with information visualization strategies and their relationship with active audience engagement in the context of health risk communication during the Covid-19 pandemic.